Is Optimal Monetary Policy Always Optimal? - Troy Davig; Refet S. Gürkaynak (Center for Economic Studies and ifo Institute (CESifo), 2015)
No. And not only for the reason you think. In a world with multiple inefficiencies the single policy tool the central bank has control over will not undo all inefficiencies; this is well understood. We argue that the world is better characterized by multiple inefficiencies and multiple policy makers with various objectives. Asking the policy question only in terms of optimal monetary policy effectively turns the central bank into the residual claimant of all policy and gives the other policymakers a free hand in pursuing their own goals. This further worsens the tradeoffs faced by the central bank. The optimal monetary policy literature and the optimal simple rules often labeled flexible inflation targeting assign all of the cyclical policymaking duties to central banks. This distorts the policy discussion and narrows the policy choices to a suboptimal set. We highlight this issue and call for a broader thinking of optimal policies.
Keywords: E61; E52; E58; E02; 330; central banking; monetary policy; fiscal policy; optimal policy; optimal policy mix